A study on bituminous coal base acid ratio to the slagging factor at large scale boiler - Samsudin, Salmi; Abdul Aziz, Nuraini; Hairuddin, Abdul Aziz; Masuri, Siti Ujila (Edizioni E.T.S., 2021)
Different types of coal have different characteristics and performances. In thermal coal plant, deposition of coal ash inside the furnace causes slag formation inside the boiler rear path and consequently reduces the heat transfer process and boiler efficiency. Besides, accumulation of ash on the boiler tube surfaces form layers of slags and blocks the flue gas flow out of the boiler. Therefore, the purpose of this study is to investigate the relationship between sub-bituminous coal base acid ratio towards the heat transfer process inside large-scale boilers. The base acid ratio for sub-bituminous coal is measured before firing inside large-scale boiler of studied the thermal plant which has a generation capacity of 700 MW. This study found correlation between high furnace rear path temperature (FRPT) that is observed to be above 800℃, with the build up of ash accumulation inside the boiler, for the studied coal. Thus, a high base acid ratio causes the accumulation of coal ash, thus reducing the heat transfer process which results in high FRPT of the boiler. Therefore, it proves that a base acid ratio is an indicator for coal performance during firing inside the boiler.